METODE PEMBEAJARAN MEMBACA DAN MENULIS AL-QUR’AN ANAK USIA DINI - Indah Sehfiani; Dwi Lestivia Tantri (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Early childhood cognitive development makes it possible to understand language quickly through memorizing meaningful words or sentences as opposed to memorizing meaningless words or sentences. Learning to write is more complex than learning to read. because writing skills require the support of the occipital lobe, auditory brain, main motor system, reflex nerves/peripheral nerves and are supported by gross motor skills. Learning is at the core of the educational process, meaning that the success of an educational process can be seen from the success or failure of the learning process. This study aims to determine the management of learning the Koran, the introduction of learning to read and write the Koran is one of the musts that must be given to early childhood as part of the Muslim community. Data collection techniques in this study were carried out by collecting and analyzing primary data sources from books, articles and research results that had been carried out by previous researchers. The data analyzed is relevant to research on learning to read and write the Koran for early childhood. findings from several references describe how the implementation of learning to read and write the Qur'an for young childe.